Regulation of Malignant Myeloid Leukemia by Mesenchymal Stem Cells - Tan, Zhenya; Kan, Chen; Wong, Mandy; Sun, Minqiong; Liu, Yakun; Yang, Fan; Wang, Siying; Zheng, Hong (Frontiers in Cell and Developmental Biology, 2022)
Bone marrow microenvironment (BMM) has been proven to have benefits for both normal hematopoietic stem cell (HSC) niche and pathological leukemic stem cell (LSC) niche. In fact, Bone marrow niche cells (i.e mesenchymal stem cells) are regulated by leukemia cells into a pathological leukemia microenvironment, and the occurrence of leukemia is also inseparable from the help of mesenchymal stem cells (MSCs). Here we summarize the detailed relationship between MSC and leukemia. MSCs can actively and passively regulate the progression of whole leukemia, drive LSCs proliferation, and inhibit physiological HSCs homeostasis which are caused by bidirectional signaling pathways and exosomes secretion. Meanwhile, the pathophysiological function of MSCs has also changed, which is heterogeneous in different leukemia types. The present review provides an up-to-date overview of the involvement of MSCs and LSCs in processes facilitating leukemia pathogenesis and progression.